2017
DOI: 10.1111/jog.13512
|View full text |Cite
|
Sign up to set email alerts
|

Association between uterine position and transvaginal misoprostol treatment for early pregnancy failure

Abstract: Uterine position has no effect on success rate of misoprostol treatment for EPF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
(45 reference statements)
2
5
1
Order By: Relevance
“…Higher may also serve as negative predictive factor for treatment success, according to additional studies (4,6,12). In agreement with our study, Chill and Vejborg (13,14) both independently reported an inverse correlation between ultrasound-calculated GA and success rate.…”
Section: Discussionsupporting
confidence: 93%
“…Higher may also serve as negative predictive factor for treatment success, according to additional studies (4,6,12). In agreement with our study, Chill and Vejborg (13,14) both independently reported an inverse correlation between ultrasound-calculated GA and success rate.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, Odeh et al 4 reported no correlation between gestational sac volume (according to three‐dimensional ultrasound) and success rate. According to the first two, 6 , 7 the current study strengthens the hypothesis that the larger the pregnancy, the greater the risk of undergoing additional surgical intervention.…”
Section: Discussionsupporting
confidence: 80%
“…The association between ultrasound findings and success rates of medical treatment for EPL was studied previously: Chill et al 7 compared 195 patients who had successful treatment with 51 patients with treatment failure and reported that in the success group, the average embryonic sac was shorter than in the failure group. Similarly, Lusink et al 6 studied 336 patients and suggested that a smaller gestational sac diameter predicts successful medical treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common medical treatment for first trimester miscarriages is misoprostol [7]. Administered vaginally, it offers success rates ranging from 70% to 90% [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%